1995
DOI: 10.1039/p29950000453
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and solution thermodynamics of complexation of alkali and alkaline-earth cations by calix[4]arene amides

Abstract: The extracting properties of nine new calix [4]arene tetraamides towards the entire alkali cation series and strontium have been determined. One of the amides bearing propargyl (prop-2-ynyl) residues on the nitrogen atoms has also been tested in complexation in methanol for the same cations. The enthalpies and entropies of complexation of alkali and alkaline-earth cations by the diethyl and pyrrolidinyl tetraamides in methanol and of alkali cations by the diethyl tetraamide in acetonitrile have been determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 6 publications
(1 reference statement)
3
45
0
Order By: Relevance
“…[62,90]. A good selectivity for Ca 2+ over Mg 2+ is achieved with tertiary amides such as 18a in electrodes (log K Ca,Mg = -1.9, FIM) [91] and with 18b in complexation (log(K Ca /K Mg ) > 7.8, MeOH) [92,93]. Ca and Sr cannot be discriminated by these ligands due to the enthalpy-entropy compensation.…”
Section: Alkaline Earth Ion Recognitionmentioning
confidence: 99%
“…[62,90]. A good selectivity for Ca 2+ over Mg 2+ is achieved with tertiary amides such as 18a in electrodes (log K Ca,Mg = -1.9, FIM) [91] and with 18b in complexation (log(K Ca /K Mg ) > 7.8, MeOH) [92,93]. Ca and Sr cannot be discriminated by these ligands due to the enthalpy-entropy compensation.…”
Section: Alkaline Earth Ion Recognitionmentioning
confidence: 99%
“…2 As far as calix [4]arene amide derivatives are concerned until then only quantitative data for p-tert-butyl-tetraacetamide, L1 and alkali-metal cations, Ag (I) and Ba (II) in methanol and Rb (I) Cs (I) and Ag (I) in acetonitrile have been reported. 74 From the information given for Ca(II) and Sr(II) in methanol (log K s ≥ 9), Li(I), Na(I) and K(I) (log K s ≥ 8.5) in acetonitrile at 298.15 K it can be concluded that high stability complexes are formed in these solvents. Since then, the only published data on receptor L1 and cations is that involving lanthanides.…”
Section: Calix[n]arene Tertiary Amide Derivatives Solution Studiesmentioning
confidence: 99%
“…As expected from the coordinating properties of the anions towards lanthanides in methanol (29), the complexes are less stable in the presence of nitrate ions than in the presence of the less coordinating 3b, these results can be compared to previous data concerning the complexation of alkaline earth cations by 3b in the same solvent. With these systems involving multicharged cations, the complexation process was also entropically controlled (31).…”
Section: Extraction Studiesmentioning
confidence: 99%